Cryopreservation of pig spermatozoa using carboxylated poly-L-lysine as cryoprotectant - Hansol JIN; Wooyoon CHOI; Kazuaki MATSUMURA; Suong-hyu HYON; Yuki GEN; Masakazu HAYASHI; Tadahiro KAWABATA; Moe IJIRI; Kazuchika MIYOSHI (The Society for Reproduction and Development, 2022)
In this study, we cryopreserved pig spermatozoa using carboxylated poly-L-lysine (CPLL) as the cryoprotectant to determine its efficacy. Pig spermatozoa were placed in a freezing extender containing 3% (v/v) glycerol and different CPLL concentrations. The motility indices of the spermatozoa cryopreserved with 0.25% (v/v) CPLL at 6 (59.3), 9 (53.7), and 12 (26.2) h after thawing were significantly higher (P < 0.01 or P < 0.05) than those of the spermatozoa cryopreserved without CPLL (53.7, 40.1, and 17.5 at 6, 9, and 12 h after thawing, respectively). The concentration of CPLL in the freezing extender did not affect the ability of frozen-thawed spermatozoa to fertilize oocytes in vitro. However, the blastocyst formation rate of embryos derived from spermatozoa cryopreserved with 0.25% CPLL (24.6%) was significantly higher (P < 0.01) than that of embryos derived from spermatozoa cryopreserved without CPLL (11.2%). The conception rate of the sows inseminated with spermatozoa cryopreserved with 0.25% CPLL (72.2%) was not significantly different from that of the sows inseminated with spermatozoa stored at 17°C (81.3%). However, the mean number of total piglets born to the former (10.0) was significantly lower (P < 0.05) than that of total piglets born to the latter (13.4). The results showed that CPLL in the freezing extender maintained the motility of frozen-thawed pig spermatozoa and improved the in vitro development of embryos produced by in vitro fertilization. In addition, we have demonstrated that piglets could be obtained with artificial insemination using spermatozoa cryopreserved with CPLL.